2005
DOI: 10.1027/0227-5910.26.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Japan

Abstract: This article introduces the reader to present conditions and suicide prevention measures in Japan. The suicide rate has increased gradually since the early 1990s, reaching a postwar peak in 1998. The number of suicides has remained at about 30,000 every year since 1998. Middle-aged (55-59 years) and elderly men have especially high suicide rates. In 2002, The Council of Learned People on Measures Against Suicides (organized by the Japanese Ministry of Health, Labor, and Welfare) released its report on national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 5 publications
1
4
1
Order By: Relevance
“…Similar findings have been shown in other studies in China and in other populations across the world[2,5,7,8,15,18]. Some factors associated with living in a rural environment that may contribute to an increased suicide rate include lower socioeconomic status, traditional belief system, and less developed social networks[5,19].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar findings have been shown in other studies in China and in other populations across the world[2,5,7,8,15,18]. Some factors associated with living in a rural environment that may contribute to an increased suicide rate include lower socioeconomic status, traditional belief system, and less developed social networks[5,19].…”
Section: Discussionsupporting
confidence: 87%
“…Suicide risk among the elderly could be a consequence of increased terminal illness, disability, and depression[6,22,23]. With regard to other suicide risk factors that have been suggested in prior studies [7,13,24,25], although we found significant associations between BMI, employment and education with suicide, these were not significant after adjustment. In addition, we document residence in north China as a risk factor and found that smoking and drinking habits were not related to suicide.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…All six prefectures in the Tohoku region (the northeastern district of the main island) and the Niigata Prefecture (a neighboring prefecture to the Tohoku region) were classified as having the highest suicide risk, whereas some prefectures in the Kanto, Kinki, and Chugoku regions (central or western districts of the main island) were classified as having the lowest suicide risk. Although it has been reported that prefectures with high suicide rates are located in the Tohoku region [43], no studies have provided suggestive evidence of emerging common ecologic effects of place where people live [44] by adjusting for individual age and occupation in each prefecture. The present study applied the same adjustment strategy across 47 prefectures throughout the study period, and it is unlikely that the widening geographical inequalities simply reflect an omitted compositional effect (e.g., health behaviors such as alcohol consumption [45][48] and smoking [49], [50], social support [51], and living arrangement [52]).…”
Section: Discussionmentioning
confidence: 99%